Faktor-Faktor Dalam Menggunakan E-Money (Gopay) Pada Masyarakat Muslim di Kota Semarang - Muhammad Faizun Ulurrosyad; Prabowo Yudo Jayanto (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2020)
Abstract  - This study aims to examine the effect of e-registration, e-filing, e-billing, service quality, understanding of taxation regulations, and tax penalties on the level of taxpayer compliance. The population in this study is 16.356 people in the area of Tax Service Office of Pratama in the city of Semarang Selatan. The sample in this study were 50 respondents obtained by the accidental sampling method. The Data were analyzed by using Structural Equation Modeling (SEM) with Partial Least Square (PLS) Path Modeling using SmartPLS 3.0 software. The results showed that e-registration, e-filing, and service quality partially affected the taxpayer compliance while e-billing, understanding of taxation regulations, and tax penalties did not affect the taxpayer compliance. The conclusion of this research is e-registration, e-filing, and service quality have a positive and significantly influence to taxpayer compliance, while e-billing, understanding of taxation regulations, and tax penalties have no influence on the level of taxpayer compliance. Keywords: Taxpayer Compliance, E-system, Understanding of Taxation Regulations